Relationship between C-Reactive Protein Levels and D-Dimer in Patients with Sepsis in the ICU of RSUD (Regional General Hospital) Prof. Dr. H. Aloei Saboe - Putri Nabila Yuniasari; Romdon Purwanto; Zuhriana K Yusuf; Sitti Rahma; Abdi Dzul Ikram Hasanuddin (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Introduction. Sepsis remains a major global health problem with high incidence and mortality, including in Indonesia. One of the key factors contributing to sepsis-related mortality is the uncontrolled activation of inflammatory and coagulation pathways. C-reactive protein (CRP) serves as a marker of inflammation, while D-dimer reflects coagulation activation. Both biomarkers are commonly elevated in sepsis and are thought to be closely associated. This study aimed to evaluate the relationship between CRP and D-dimer levels in sepsis patients treated in the Intensive Care Unit (ICU) of RSUD Prof. Dr. H. Aloei Saboe. Methods. This analytic observational study employed a cross-sectional design and was conducted in the ICU of RSUD Prof. Dr. H. Aloei Saboe from July to November 2025. A total of 48 sepsis patients were included using total sampling based on medical record data from January to December 2024. The relationship between CRP and D-dimer levels was analyzed using the Pearson correlation test. Results. All patients showed elevated CRP levels (100%), and most had increased D-dimer levels (97.9%). Bivariate analysis demonstrated a statistically significant positive correlation between CRP and D-dimer levels, with a correlation coefficient of +0.333, indicating a weak to moderate association. Conclusion. There is a significant positive correlation between CRP and D-dimer levels in sepsis patients in the ICU of RSUD Prof. Dr. H. Aloei Saboe. Higher CRP levels tend to be accompanied by increased D-dimer levels, reflecting the interplay between inflammation and coagulation activation in sepsis.